Individual, Workplace, and Combined Effects Modeling of Employee Productivity Loss. Issue 6 (June 2019) - Stepanek, Martin; Jahanshahi, Kaveh; Millard, Francois
Abstract : Objective: Systematically and simultaneously investigate a wide range of influences on workplace productivity loss. Methods: Data were collected from 31, 950 employees in the UK. Influences of employees' socioeconomic characteristics, lifestyle, commuting, physical and mental health, well-being, and job and workplace environment were assessed using structural equation models, allowing systematic decomposition of the complex network of influences and creating new, deeper insights. Results: Mental health, physical health, job characteristics, and support from organization are the most important (direct or indirect) determinants of employees' productivity. 93% of the indirect influences are mediated through mental and/or physical health. Some influences that appear as strong predictors in simple models lose most of their explanatory power in more complex models with additional explanatory variables. Conclusions: There is a need for a more tailored strategy to improve employees' wellbeing as well as the overall organizational, work, and management culture. Abstract : Supplemental Digital Content is available in the text